2013
DOI: 10.1021/nl4020952
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Formation of Noncrystalline Li2O2 in the Li–O2 Battery with RuO2 Nanoparticles

Abstract: Low electrical efficiency for the lithium-oxygen (Li-O2) electrochemical reaction is one of the most significant challenges in current nonaqueous Li-O2 batteries. Here we present ruthenium oxide nanoparticles (RuO2 NPs) dispersed on multiwalled carbon nanotubes (CNTs) as a cathode, which dramatically increase the electrical efficiency up to 73%. We demonstrate that the RuO2 NPs contribute to the formation of poorly crystalline lithium peroxide (Li2O2) that is coated over the CNT with large contact area during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
427
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 445 publications
(454 citation statements)
references
References 44 publications
25
427
2
Order By: Relevance
“…Compared with the pure Ag NWs, the AgPd-3 NTs show improved round-trip effi ciency up to 78%, which is vital for electrochemical energy storage devices, together with a discharge capacity of 2650 mA h g −1 and a charge capacity of 2600 mA h g −1 at a current density of 0.2 mA cm −2 . Furthermore, the charge plateau of the AgPd-3 NTs is at 3.69 V, lower than those of the Ag NWs and some previously reported results, [ 16,[46][47][48] showing the excellent OER performance. These results can also be further confi rmed by the CVs and RDE curves in O 2 saturated nonaqueous electrolyte (1 M LiCF 3 SO 3 in tetraethylene glycol dimethyl ether (TEGDME)), as shown in Figure S5 (Supporting Information).…”
Section: Doi: 101002/adma201502262contrasting
confidence: 60%
See 1 more Smart Citation
“…Compared with the pure Ag NWs, the AgPd-3 NTs show improved round-trip effi ciency up to 78%, which is vital for electrochemical energy storage devices, together with a discharge capacity of 2650 mA h g −1 and a charge capacity of 2600 mA h g −1 at a current density of 0.2 mA cm −2 . Furthermore, the charge plateau of the AgPd-3 NTs is at 3.69 V, lower than those of the Ag NWs and some previously reported results, [ 16,[46][47][48] showing the excellent OER performance. These results can also be further confi rmed by the CVs and RDE curves in O 2 saturated nonaqueous electrolyte (1 M LiCF 3 SO 3 in tetraethylene glycol dimethyl ether (TEGDME)), as shown in Figure S5 (Supporting Information).…”
Section: Doi: 101002/adma201502262contrasting
confidence: 60%
“…The XRD patterns in Figure 4 c also confi rm the reversible formation of Li 2 O 2 during the discharge and charge processes, which is consistent with the results obtained by TEM observation and other groups. [ 46,47,51,52 ] The diagram in Figure 4 e schematically outlines the discharge and charge processes. The NT structure with porous channels, facilitating rapid O 2 and electrolyte diffusion, forms a continuous conductive network throughout the whole ORR and OER process.…”
Section: Communicationmentioning
confidence: 99%
“…S5). The majority of the CNTs have a smooth surface without the coverage of Li2O2 [20,22,61,62]. The low Li2O2 coverage region might induce localized distribution of Li2O2 on the cathode, and eventually aggravates the electrode polarization.…”
Section: Resultsmentioning
confidence: 99%
“…The uniform distribution of nanosized Li2O2 intimately contacting with highly conductive CNTs facilitate the smooth decomposition across large interface area at lower charge potential and thus the Li2O2 could be sufficiently decomposed after charging (Fig. 4d) [2, 30,61,63]. After 10 th discharge, the structure of Fe@NCNT is well preserved (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, Chen and co‐workers and Byon and co‐workers both demonstrated that upsizing Li 2 O 2 would result in a higher charging plateau and low charging rate 13, 14. That is, for large Li 2 O 2 aggregations, a contradiction between high capacity and low oxygen evolution reaction (OER) overpotential is found.…”
Section: Introductionmentioning
confidence: 99%